DEVELOPMENT OF CREATIVE INDIVIDUALITIESOF STUDENTS OF FACULTIES OF ARTS BY MEANS OF DESIGN TECHNOLOGIES - Хайє, Лян Хайє (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is sanctified to illumination of specific of development of creative individuality of students of faculties of arts in the process of professional preparation. Application of project technologies offers as an innovative form of professional preparation of future music masters. In the article examined functional maintenance of process of forming of readiness of future music masters to vocally-choral work with application of project technologies. Taking into account the specific of vocally-choral preparation, it is well-proven the author of the article, that in the totality these functions assist optimization of process of forming of creative individuality of students of faculties of arts